Fatigue life of laser clad hardfacing alloys on AISI 4130 steel under rotary bending fatigue test. (March 2015) - Hutasoit, Novana; Luzin, Vladimir; Blicblau, Aaron; Yan, Wenyi; Brandt, Milan; Cottam, Ryan
Highlights: Tensile residual stress in coating area reduced fatigue of laser clad specimen. Stellite 6 coating generated longer fatigue life compared to the Deloro 40G coating. Increasing the coating thickness reduced the fatigue life of laser clad specimens. Abstract: Fatigue life study of structures constructed by laser cladding using two types of hardfacing alloy, Stellite 6 (Co base) and Deloro 40G (Ni base) on AISI 4130 steel substrate was conducted using rotary bending fatigue test at ambient temperature 20 °C. The laser clad specimens showed a reduced fatigue life compared to the specimen without cladding but of the same size due to the presence of residual stresses in substrate and coating regions. The presence of higher compressive residual stresses in substrate region and lower tensile residual stress in coating region of specimen laser clad with Stellite 6 generated longer fatigue life compared to the specimens laser clad with Deloro 40G, at a similar coating thickness level. With the same final structure size, coating thickness produced an inversely proportional effect on fatigue life where thinner coatings result in less reduction of fatigue life compared to thicker coating. The analytical model employed in this study demonstrated that thinner coatings alters axial residual stress by generating lower tensile residual stress in coating region which enhance fatigue life, compared to thicker coatings. This work has demonstrated the influence of coating type, coating thickness and load level on the fatigue life of the laser clad structures.